Strategic business improvement plan: the case of Teratak Coklat / Rosli Othman, Mohd Suri Shafie and Mohd Zaidy Omar - Othman, Rosli; Shafie, Mohd Suri; Omar, Mohd Zaidy (2015)
Food processing industry has become developed rapidly since the era of industrial development of the country. In terms of the business potential to becoming as very strategic business industry, this food industry is dominated by small and medium scale firm. Teratak Coklat Company does not lag behind. The organization is required to identify the way, the most effective strategy to provide the maximum degree of improvement and attain high profit levels and to go as the best Halal food producer. Therefore, a study needs to be conducted and established to identify problems faced by Teratak Coklat by using data from websites and Teratak Coklat. The instrument used to collect primary data is interviewed. The interview questions were used to collect information from the staff and management of the Teratak Coklat to conduct analysis using Porter's Five Forces, SWOT Analysis, TOWS analysis and ANSOFF matrix analysis. The researcher had also obtained some data from Teratak Coklat company profile and sales ledger. For external secondary data, the data were collected from relevant website. Financial tools were used to determine strategies for the company to enhance its competitive advantage in the food industry. To understand the firm financial results and trends, financial ratios analysis is used such as profitability ratio.